2011
DOI: 10.1111/j.1468-1331.2010.03148.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1: genetic susceptibility and disability progression in a Spanish multiple sclerosis population

Abstract: HLA-DRB1*15 is associated with MS when comparing patients with unrelated healthy controls in a Spanish population. The HLA-DRB1*01 and HLA-DRB1*04 alleles are related to a worse prognosis when considering the time taken to reach severe disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 55 publications
5
37
1
Order By: Relevance
“…In contrast, the HLA-B*44:02 allele, that is proposed to be protective for MS susceptibility, may reduce the radiographic burden of disease on T2-weighted brain MRI (Healy et al, 2010). A consistent impact of HLA alleles on MS neurologic impairments, as measured by expanded disability status scale progression, has not been found (Marrosu et al, 1988;Romero-Pinel et al, 2011). Interestingly, a spontaneously occurring null allele of the HLA-DRB5 gene located telomeric to HLA-DRB1 might contribute to MS severity (Caillier et al, 2008).…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…In contrast, the HLA-B*44:02 allele, that is proposed to be protective for MS susceptibility, may reduce the radiographic burden of disease on T2-weighted brain MRI (Healy et al, 2010). A consistent impact of HLA alleles on MS neurologic impairments, as measured by expanded disability status scale progression, has not been found (Marrosu et al, 1988;Romero-Pinel et al, 2011). Interestingly, a spontaneously occurring null allele of the HLA-DRB5 gene located telomeric to HLA-DRB1 might contribute to MS severity (Caillier et al, 2008).…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…We have shown that several genotypes containing the HLA-DRB1*15 allele are associated with MS susceptibility in our cohort. We demonstrated the association of the disease with the HLA-DRB1*15 allele [20]. The association of MS with DRB1*15 has been well established [3] although it is known that the interaction of this allele with other alleles as well as other loci and even with environmental factors play an important role in increasing or decreasing the MS susceptibility.…”
Section: Discussionmentioning
confidence: 94%
“…The DRB1*03/15 genotype was also significantly more frequent in patients than in controls although when we considered each allele independently from the other, the DRB1*03 allele did not reach significance after multiple testing correction [20]. The DRB1*03 allele had been found related with MS susceptibility in several cohorts [22][23][24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other authors claim that OCBs can determine better disability status [14]. Koch et al found that there was no relation between OCBs and disability, as well as RR MS form tendency to change to SP form [18], in addition, L. Romero-Pinel et al suggest that HLA DRB1 alleles have no impact on MS course change [24].…”
Section: Discussionmentioning
confidence: 99%